KURIKULUM PENDIDIKAN AGAMA ISLAM PENDEKATAN MULTIDISIPLINER, INTERDISIPLINER DAN TRANSDISIPLINER DI PERGURUAN TINGGI - Bassam Abul A'la; Sugito Muzaqi; Miftahul Alimin (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
Islamic religious education is an integration of education and Islamic sciences. It is included in the category of multidisciplinary disciplines. Given the diversity of approaches and different applications from each institution, it seems important to identify a model of Islamic religious education curriculum based on a multidisciplinary, interdisciplinary, and transdisciplinary (MIT) approach. Therefore, by using the systematic literature review (SLR) method and Nvivo 12 as a qualitative data processing tool, this study seeks to examine the various integrated approach models and their application in the curriculum of Islamic religious education in tertiary institutions. The result of this research is that there is one curriculum model that is widely used in the application of the MIT approach in the Islamic religious education curriculum, namely collaboration.